2018
DOI: 10.1002/we.2187
|View full text |Cite
|
Sign up to set email alerts
|

Scour influence on the fatigue life of operational monopile‐supported offshore wind turbines

Abstract: Offshore wind turbines supported on monopiles are an important source for renewable energy. Their fatigue life is governed by the environmental loads and in the dynamic behavior, depending on the support stiffness and thus soil‐structure interaction. The effects of scour on the short‐term and long‐term responses of the NREL 5‐MW wind turbine under operational conditions have been analyzed by using a finite element beam model with Winkler springs to model soil‐structure interaction. It was found that due to sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…If this is not addressed in a suitable way and just in time, the scour phenomenon can cause operational unavailability, changes in the natural frequencies of the soil-structure system [12], fatigue life reduction [13], and even in extreme cases the collapse of the structure [14]. There is a significant need to advance in this field and therefore, it is very important to carry out some researches about scour.…”
Section: Number Of Farmsmentioning
confidence: 99%
“…If this is not addressed in a suitable way and just in time, the scour phenomenon can cause operational unavailability, changes in the natural frequencies of the soil-structure system [12], fatigue life reduction [13], and even in extreme cases the collapse of the structure [14]. There is a significant need to advance in this field and therefore, it is very important to carry out some researches about scour.…”
Section: Number Of Farmsmentioning
confidence: 99%
“…Note that time-varying stiffness/damping properties of the soil due to long-term cyclic loading [93,94] and scour depth variation due to backfilling are not accounted for. Rezaei et al [95] presented a study of scour and backfilling effects on the FL of a 5 MW monopile supported OWT, using quasistatic, modal, and time-domain fatigue analyses. It was demonstrated that a scour depth of 1.5D could result in a 45% reduction of the FL of the wind turbine structure.…”
Section: Natural Frequency and Fatigue Life (Fl)mentioning
confidence: 99%
“…For structural designers it is convenient to characterise the aerodynamic damping using a linear damping ratio associated with the first vibrational mode of the tower, as this allows the dynamic response of the system to be calculated rapidly, e.g. for fatigue analyses [10]. Specific studies of the aerodynamic damping have generated experimental or analytical modal damping ratios that capture this source of dissipation [11].…”
Section: Introductionmentioning
confidence: 99%
“…For OWTs, the aerodynamic damping values quoted below were obtained by subtracting an assumed underlying damping of 2% from the measured total damping [15]. For onshore wind turbines, the total damping is a closer approximation of the aerodynamic damping [10] as foundation damping is low. Hansen et al [16] estimated the aerodynamic damping in a 2.75 MW operating OWT using two experimental methods.…”
Section: Introductionmentioning
confidence: 99%